Mental disability, the European Convention on Human Rights and Fundamental Rights and Freedoms, and the Sustainable Development Goals - Bartlett, Peter (Routledge, 2017)
Since Winterwerp v the Netherlands in 1979, the European Court of Human Rights and, later, the European Committee for the Prevention of Torture, have been developing law and policy on human rights and mental disability (taken in this chapter to include psychosocial disability/mental health problems, and mental disabilities related to old age). This paper charts the shape of those developments, relating to psychiatric detention, psychiatric treatment, and systems of guardianship. The new paradigm of human rights, manifest in both the United Nations Convention on the Rights of Persons with Disabilities (CRPD) and the 2015 United Nations Sustainable Development Goals (SDGs) is explored, and the potential and limitations of the ECHR in advancing that new agenda considered.